PENGETAHUAN DAN SIKAP TENTANG POSYANDU LANSIA DENGAN KEAKTIFAN LANSIA DATANG KE POSYANDU DI DESA PULONASIR KECAMATAN BARENG KABUPATEN JOMBANG: PENGETAHUAN DAN SIKAP TENTANG POSYANDU LANSIA DENGAN KEAKTIFAN LANSIA DATANG KE POSYANDU DI DESA PULONASIR KECAMATAN BARENG KABUPATEN JOMBANG - Yusanti, Devi Chintya (WELL BEING, 2017)
The elderly posyandu is an integrated service post for the elderly community. The elderly are not active enough in utilizing health services at the posyandu for the elderly, so that their health condition cannot be monitored properly, so that if they experience a risk of disease due to deterioration of their body condition and the process of experiencing it, it is feared that it can be fatal and threatening their lives. The purpose of this study was to determine the knowledge, attitudes and activeness of the elderly coming to the posyandu in Pulonasir Village, Bareng District, Jombang Regency. In this study, the researcher used a correlational analytic research design with a cross sectional approach and the Spearman rank test using SSS 16. The sample size was 30 respondents and the sampling technique was total sampling where the sample was the elderly who attended the elderly posyandu in Pulonasir Village, Bareng District, Jombang Regency. The results showed that the knowledge of the elderly was sufficient for 14 respondents (46.7%), 16 respondents (66.7%) had negative attitudes who visited the posyandu (53.3%), 20 respondents (66.7%) who were not active in visiting the posyandu. The knowledge obtained was p = 0.00 where <0.05, while the attitude was p = 0.074 where p <0.05 so that there was no relationship between knowledge and attitude of the elderly with activeness in coming to the posyandu for the elderly. This shows that activeness can affect the level of knowledge of the elderly when they come to the elderly posyandu, but attitudes cannot affect the activeness of the elderly when they come to the elderly posyandu.